Single-dose rituximab for remission induction and maintenance therapy in ANCA-associated vasculitis: a retrospective analysis of 17 patients. (November 2014) - Moog, P; Probst, M; Kuechle, C; Hauser, C; Heemann, U; Thuermel, K
<x xml:space="preserve">Abstract</x> Objectives: The aim of this study was to evaluate the efficacy of a repeated single-dose rituximab (RTX) regimen for remission induction and maintenance in anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV). Method: We performed a retrospective analysis of all patients with an established diagnosis of AAV who were treated with single-dose RTX infusions at our institution. Clinical outcome data were assessed over a period of 24 months. Results: Sixteen patients were treated for remission induction and maintenance and one patient was treated for only maintenance therapy. Remission (absence of disease activity during the past 3 months and a prednisolone dose of ≤ 7.5 mg) was achieved in 11 patients (68%) with a mean time to remission of 9.4 (range 3–24) months. At 6 months, six patients (37.5%) were in remission and the mean prednisolone dose of all responding patients was 8.2 mg. Five patients had treatment failure due to early relapsing (n = 4) or persistently active (n = 1) disease. At 24 months, nine of the 11 responding patients (82%) were in remission. All patients still had concomitant steroid and/or disease-modifying anti-rheumatic drug (DMARD) therapy at 24 months. Overall, 11 relapses were seen in nine patients (five non-responders and four responders) with a mean time to relapse of 5.3 (range 4–24) months. No major relapses were observed in the responding patients. Severe infections were only seen in patients who had been previously treated with cyclophosphamide (CYC). Conclusions: The combination of single-dose RTX with other immunosuppressants seems less effective than the standard RTX regimen for the induction of remission of AAV.